FECAL IMPACTION IN A PYTHON (BOA CONSTRICTOR) - CASE REPORT - Barros Albuquerque, Isaac Manoel (2013)
It is reported the case of an adult python (Boa constrictor) with signs of anorexia, lethargy and no bowel movements for about two months. According to the clinical history, the animal was fed with small amphibians, rats and ground beef. On the clinical evaluation was palpated a firm distention of the coeloic cavity. Through simple radiography was detected 13 radiopaque structures in the final third of the coelomic cavity. The diagnosis was intestinal obstructions due to fecalomas. The initial treatment consisted in oral and transrectal mineral oil; however, without success. Then, an enterotomy was performed and 365 g of fecal content was removed. After surgery, antibiotic therapy using enrofloxacin (10 mg/kg, im) and ketoprofen (2 mg/kg, im) as anti-inflammatory were administered. Also, mineral oil was orally administered (1 mg/kg) to promote intestinal transit.